Rediscovery of two casts of the historically important ‘Proteo-saurus’, the first complete ichthyosaur skeleton - Dean R. Lomax; Judy A. Massare (Royal Society Open Science, 2022)
The first complete ichthyosaur skeleton was introduced to the scientific community in 1819 by Sir Everard Home, and given the name Proteosaurus, although the name was subsequently replaced by ‘Ichthyosaurus’. The skeleton is from Lyme Regis and was probably collected by Mary Anning as it was in the collection of Colonel Birch. The specimen ultimately ended up in the collection of the Royal College of Surgeons, London, where it was destroyed in a bombing raid during World War II. We have discovered two plaster casts of the specimen, although no record exists of casts ever being made. The casts are at the Peabody Museum, Yale University, USA and the Museum für Naturkunde, Berlin, Germany. Significantly, these verify the accuracy of the published drawing of the specimen, and clarify morphologies of some of the bones. Discrepancies between the drawing and the casts are mainly in the details of the forefins and hindfins. The specimen can be assigned to Ichthyosaurus, but the species cannot be determined. This case illustrates the importance of old casts in museum collections. Additional, yet unrecognized casts of this specimen might exist in the UK or elsewhere.